Long Non-coding RNA LINC00115 Contributes to the Progression of Colorectal Cancer by Targeting miR-489-3p via the PI3K/AKT/mTOR Pathway - Feng, Weiyu; Li, Baodong; Wang, Jinbang; Zhang, Huiliang; Liu, Yonggang; Xu, Dongli; Cheng, Ke; Zhuang, Jing (Frontiers in Genetics, 2020)
Long noncoding RNAs (lncRNAs) are tumor-related regulators and have been found to be involved in the underlying molecular mechanisms of colorectal cancer (CRC). However, the role of lncRNA LINC00115 during CRC progression is not entirely elucidated. In this study, we discovered that LINC00115 was significantly overexpressed in CRC and its overexpression predicted poor patient outcomes. Downregulation of LINC00115 markedly inhibited CRC cell proliferation, increased cell apoptosis, and suppressed cell migration and invasion. Moreover, downregulation of LINC00115 led to the inactivation of PI3K/AKT/mTOR signaling. Bioinformatics analysis identified miR-489-3p as a candidate target of LINC00115. Furthermore, we revealed an inverse correlation between LINC00115 and miR-489-3p in CRC tissues. Importantly, by luciferase reporter assay, we found that miR-489-3p might directly target LINC00115 and downregulation of miR-489-3p could rescue the biological effects induced by the absence of LINC0015. In conclusion, our findings demonstrated that LINC00115 serves as an oncogene in CRC metastasis. Deeper understanding of the LINC00115/miR-489-3p axis might provide potential therapeutic targets against CRC metastasis.